Desenvolvimento de procedimentos para a determinação de enxofre em diesel, biodiesel e óleo lubrificante usando ICP OES e ICP-MS - Amais, Renata Stábile (2014)
Since 1990 concerns about environmental and public health have stimulated the restrictions of maximum sulfur content in fuels allowed by legislation, especially in diesel and biodiesel, by several governmental agencies. The focus of this thesis was the development of sample preparation strategies for fuels and the determination of sulfur using inductively coupled plasma techniques, such as optical emission spectrometry (ICP OES) and mass spectrometry (ICP-MS). Difficulties associated to each technique were evaluated and strategies to overcome them were proposed. Studies on sample preparation based on microwave-assisted heating in closed vessels using diluted nitric acid solution and microemulsions were carried out for further S determination by ICP OES. The strategy of summation of the intensities of multiple sulfur emission lines allowed for 2-fold higher sensitivity for S determination by ICP OES and the instrumental limit of detection for S I 181,972 nm and S I 180,669 nm emission lines combination was 0.42 mg L-1. The interference standard method (IFS) was proposed and thoroughly evaluated to overcome polyatomic interferences on sulfur determinations by low-resolution ICP-MS. Applying this strategy the accuracy for S determination by ICP-QMS was achieved without any instrumental modification or introduction of reaction or collision gases. Recoveries from 92.6 to 99.7 % were obtained for S determination in lubricating oil CRM and addition and recovery experiments in biodiesel by using the isotope 36Ar+ as IFS. Evidences of principle, potentialities and limitations of IFS method were investigated using a double focused sector field inductively coupled plasma mass spectrometry (SF-ICP-MS). The hypothesis that polyatomic interfering ions and IFS species (36Ar+, 36ArH+ and 38Ar+) experience similar fluctuations in plasma was confirmed. More advanced instrumental arrangements, such as SF-ICP-MS and tandem mass spectrometry (ICP-MS/MS), were also evaluated for sulfur determination in fuels. Under optimized conditions, instrumental limits of detection for S determination via 32S16O+ and 34S16O+ by ICP-MS/MS were 0.33 and 0.78 μg L-1, respectively, and recoveries from 102 to 113 % were obtained for S determination in biodiesel, diesel and lubricating oil CRMs. The combination of sample preparation employing microwave-assisted acid digestion with diluted nitric acid, determination by SF-ICP-MS and isotope dilution method allowed the determination of a total S concentration of 9.06 ± 0.13 μg g-1 in a diesel sample candidate to certified reference material.